The Performance of Ruwatan in Javanese Community: An Anthropolinguistic Approach - Rahmawati; Sibarani, Robert; Lubis, Tasnim (Tradition and Modernity of Humanity, 2022)
This study focused on the Ruwatan (cleaning the village) Performance of the Javanese community. The objective of the research was to find out the pattern of Ruwatan performance in the Ruwatan activity (cleaning the village) of the Javanese community through the concept of an anthropolinguistic approach that includes text, co-text, and context. further, it is used to describe the structure, stages, performance components, and functions of Ruwatan speech. The research data were video recordings, in-depth interviews and participatory observations. The method in this study using ethnography proposed by Spradley (1979, 1980) was applied in this study from data collection to analysis. The results showed that the Ruwatan performance contained in the Ruwatan process of the Javanese community was the performance of religion, tranquillity, order and comfort. The puppeteer's performance is the performance of acting as an intermediary between the human realm and the supernatural or supernatural realm by using offerings and spells containing supernatural powers in instructing, informing, and pleading with the Almighty.